Checklist of bats from the Sungai Rawog conservation area, Segaliud Lokan forest reserve, Sabah, Malaysia - Lawrence Alan Bansa; Nur Ain Awatif Mohd-Kanapiah; Mohamad Muhaymin Mohamad Zakri; Azniza Mahyudin; Noor Haliza Hasan (Sabah Forestry Department, 2024)
This report provides the bat species list from the Sungai Rawog Conservation Area (SRCA), Segaliud Lokan Forest Reserve (FMU 19B), Sabah, Malaysia. Objective of the study is to identify the bat diversity in the area and the role of SRCA as their refuge on the east coast of Sabah. A four-night bat survey was conducted from the 8th to the 11th of June 2023 at five trails (trail 6, 8, 9, 10 and 12) in compartment 56 of the FMU 19B using at least six mist nets and three harp traps. Findings of this survey recorded a total of 26 individual understorey bats from 10 species, represented by 4 species of Rhinolophidae (Rhinolophus trifoliatus, R. acuminatus, R. borneensis, and R. sedulus), 2 species of Hipposideridae (Hipposideros ridleyi and H. ater), 2 species of Vespertilionidae (Kerivoula papillosa and K. intermedia), and 1 species of Nycteridae (Nycteris tragata). Despite the lower bat species diversity compared to the previous bat survey in compartment 61, this survey was still able to record the IUCN Red List Vulnerable (VU) species (H. ridleyi), along with three Near Threatened (NT) species (R. trifoliatus, R. sedulus, and K. intermedia), while the rest are of Least Concern (LC). Additionally, this survey highlighted three additional bat species in the area, namely R. luctus, H. ater and N. tragata. This report highlights the important role of SRCA FMU 19B as a refuge for bats and other forest-specialist mammals, thereby supporting the effectiveness of landscape planning in the area.